Symptoms and clinical signs associated with hospital admission and mortality for heart failure - Devroey, Dirk; Van Casteren, Viviane (Central European journal of public health, 2010)
Little information is available on the predicting factors for hospitalisation and mortality in heart failure. The aim of this study was to determine the symptoms and clinical signs at the time of the diagnosis of heart failure that predict hospitalisation within the first month after diagnosis and mortality within the first six months after diagnosis. Data were prospectively collected during a two-year period by a nationwide network of sentinel family practices. All adult patients for whom the first time the diagnosis of heart failure was clinically suspected were registered. One, six and twelve months after the initial diagnosis, the family physicians completed a follow-up form with questions about the final diagnosis, evolution and outcome. In total 557 patients with confirmed heart failure were recorded (median age = 78 years). Hospitalisation within the first month after the diagnosis was best predicted by peripheral oedema (p = 0.001), nocturnal dyspnoea (p = 0.022) and pleural effusion (p = 0.032) at the time of the diagnosis. Six months after the initial diagnosis the mortality was 19% and after 12 months it was 26%. Mortality within the first six months after the diagnosis was best predicted by age (p < 0.001) and pulmonary rales (p = 0.001). Peripheral oedema appeared more among the survivors (p = 0.035). Peripheral oedema, nocturnal dyspnoea and pleural effusion are highly associated with hospitalisation within the first month after diagnosis.
Keywords: dospělí; Hospitals; Female; Prevalence; nemocnice; Adult; ženské pohlaví; Heart Failure; Sentinel Surveillance; Time Factors; časové faktory; lidé; srdeční selhání; Patient Admission; Aged, 80 and over; příjem pacientů; sentinelová surveillance; prevalence; prospektivní studie; Male; Aged; Prospective Studies; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans